La nòva cançon occitana e la societat miègjornala - Yan Lespoux (Lengas)
From the end of the 1960s onwards, the Nouvelle chanson occitane (NCO) became an important vehicle for the transmission of occitanist themes in southern society. In return, it also echoed the social struggles that were being waged in the Oc region during this period. The work of Claude Marti and his commitment, in particular to the struggle of the Languedoc winegrowers, illustrates this movement quite well.